Macro–Micro Failure Characteristics of Soft–Hard Composite Rock with Unparallel Joints: Analysis Based on DIC and AE Technique - Xinglong Feng; Su Li; Chaoyi Yang; Zhengrong Li; Hang Lin; Zeyue Wang (Applied Sciences)
Jointed composite rock masses are ubiquitous, where the interplay between fractures and bedding planes significantly complicates their failure mechanisms. This study conducted uniaxial compression tests on a composite rock material featuring soft and hard components with unparallel double joints. Leveraging the digital image correlation (DIC) method and acoustic emission (AE) technology, the investigation analyzed the influence of joint angles on the mechanical properties, failure modes, and crack propagation behaviors. The results indicate that the peak strength exhibits an ascending–descending–ascending trend with the variation of upper joint angle, peaking at 90°. The failure modes can be systematically categorized into three types. The failure of the specimen is predominantly influenced by the upper joint. However, when the lower joint angle is relatively flat, it becomes more prone to contributing to the failure of the specimen. The lower joint-dominated failure mode only occurs when the upper joint angle is 90°. As the lower joint angle remains at 90°, an augmentation in the upper joint angle initially leads to a decrease and subsequently to an increase in the proportion of shear cracks. In contrast, when the lower joint angle deviates from 90°, the increase of the upper joint angle initially boosts and then diminishes the proportion of shear cracks.